Stratified Saline Flume Experiments on the Entrainment Process of the Atmospheric Convective Boundary Layer With Vertical Wind Shear - Li, A.; Lin, W.; Gao, W.; Liu, T.; Xia, Y. (Frontiers in Environmental Science, 2022)
A stratified saline flume experimental apparatus was set up in this study to simulate experimentally the entrainment process of the atmospheric convective boundary layer with vertical wind shear, of which the entrainment characteristics are quite different from those of shear-free convective boundary layer. Entrainment occurs at the interface of the flume inlet until the velocity difference between the upper and lower layers reaches 0.04 m/s, and a stable entrainment thin zone is formed after 12zi distance from the flow inlet, where zi is the height of the entrainment zone. Shear in the entrainment zone induces the anti-gradient momentum transport process, and a series of large-scale vortices with a characteristic length of about (1.0 ~ 1.5)zi fills this region. The data analysis shows that the velocity difference and buoyancy flux of the bottom plume promote the occurrence of entrainment, while the density difference between the upper and lower layers inhibits it. The contribution of the shear effect to the entrainment process was introduced into the characteristic velocity scale, and a new scaling relation between the dimensionless thickness of the entrainment zone and the corrected Richardson number was obtained as Δz/zi = 1.17RiNC-1/2 from the experimental results, which agrees well with the available radar data and the numerical simulation data.